Hydroamination of terminal alkynes with secondary amines catalyzed by copper: regioselective access to amines. Issue 56 (16th June 2015) - Bahri, Janet; Blieck, Rémi; Jamoussi, Bassem; Taillefer, Marc; Monnier, Florian
Abstract : A simple and convenient copper-catalyzed hydroamination of arylacetylenes with secondary amines has been performed giving a simple access to aliphatic amines after reduction of the hydroaminated products ( E -enamines). Abstract : A simple and convenient copper-catalyzed hydroamination of arylacetylenes with secondary amines has been performed giving a simple access to aliphatic amines after reduction of the hydroaminated products ( E -enamines). Here we described a mild catalytic system utilizing CuCN precatalyst without any additive ligands in a solvent-free system.